Ultraviolet light-induced decomposition of benzothiophene and dibenzothiophene derivatives for efficient sulfur removal without additives and catalysts. (10th October 2022) - Shinozaki, Taka-Aki; Suenaga, Masahiko; Ko, Yohan; Yamamoto, Eiji; Murayama, Haruno; Tokunaga, Makoto
Abstract: When producing liquid fuels from petroleum, hydrodesulfurization methods reduce the concentration of sulfur to ≤10 mg(S)/L (weight/volume concentration of sulfur), namely, ≤ 0.31 mmol/L. Dibenzothiophene derivatives (DBTs), which are known as particularly difficult desulfurizing substances, have been decomposed reductively in severe conditions of high temperatures (270–372 °C) and high pressure (50–102 atm of H2 ). In this study, we developed a UV light irradiation-based desulfurization method for aromatic sulfur compounds such as benzothiophene derivatives (BTs) and DBTs under room temperature and atmospheric pressure without the use of catalysts or additives. This method is simple, location-independent, and low-cost, and has low environmental impact. BTs and DBTs completely decomposed in approximately 8 h and 16 h, respectively, under ultraviolet (UV) light irradiation ( λ  = 254 nm) from a 8 W lamp. The yellow precipitates that were produced upon decomposition were confirmed to be sulfur allotropes (S n ). The residual hydrocarbon portion of DBT after sulfur removal was determined to be benzene. The decomposition reaction was determined to exhibit pseudo-first-order reaction. DFT calculations confirmed the degradation mechanism as follows: UV light irradiation induces a photochemically excited triplet state of DBTs. The excited DBTs reacts with O2 to form a π-complex, which isomerizes to a more stable σ-complex. The DBTs-O2 (σ-complex) then reacts with free DBTs to afford two molecules of dibenzothiophene-5-oxide derivatives (DBTOs), which are excited to singlet states on photoirradiation. The excited DBTOs isomerize through a minimum energy intersection eventually to dibenzofuran episulfides from which sulfur extrusion occurs. Graphical abstract: Image 1 Highlights: A desulfurization method was developed under room temperature and atmospheric pressure conditions using UV light irradiation ( λ  = 254 nm) from an 8 W lamp without the use of catalysts or additives. The sulfur content in benzothiophene and dibenzothiophene derivatives was successfully removed in the form of sulfur allotropes (S n ). Kinetic experiments revealed that the effect of substituents on the decomposition rate of dibenzothiophene is different in UV desulfurization and hydrodesulfurization. DFT calculations for the decomposition mechanism were consistent with experimental results.